Seasonal and interannual variations in ice melange and its impact on terminus stability, Jakobshavn Isbræ, Greenland. Issue 225 (2015) - Cassotto, Ryan; Fahnestock, Mark; Amundson, Jason M.; Truffer, Martin; Joughin, Ian
Abstract: We used satellite-derived surface temperatures and time-lapse photography to infer temporal variations in the proglacial ice melange at Jakobshavn Isbræ, a large and rapidly retreating outlet glacier in Greenland. Freezing of the melange-covered fjord surface during winter is indicated by a decrease in fjord surface temperatures and is associated with (1) a decrease in ice melange mobility and (2) a drastic reduction in iceberg production. Vigorous calving resumes in spring, typically abruptly, following the steady up-fjord retreat of the sea-ice/ice-melange margin. An analysis of pixel displacement from time-lapse imagery demonstrates that melange motion increases prior to calving and subsequently decreases following several events. We find that secular changes in ice melange extent, character and persistence can influence iceberg calving, and therefore glacier dynamics over daily-to-monthly timescales, which, if sustained, will influence the mass balance of an ice sheet.